2022
DOI: 10.1002/lary.30038
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on Triple Endoscopy Data Elements Preparatory to Development of an Aerodigestive Registry

Abstract: Objectives/Hypothesis: This study defines essential data elements to be recorded during an aerodigestive "triple endoscopy" to form the foundation of a standardized multicenter registry and to clearly define measurement of each consensus item.Study Design: Modified Delphi process.Methods: Modified Delphi consensus with six survey rounds. Twenty-four expert pediatric otolaryngology, pulmonology, and gastroenterology aerodigestive clinicians from eight large academic pediatric aerodigestive programs formed the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…With the growth of multidisciplinary aerodigestive centers, many patients with persistent pulmonary symptoms undergo triple airway endoscopy as an initial part of their workup before consideration of chest CT. 49 This approach commonly includes flexible bronchoscopy with bronchoalveolar lavage and the results are typically interpreted in the multidisciplinary aerodigestive context. 8,[12][13][14] Prior studies have shown an association between bronchiectasis and BAL neutrophil count and the results our ROC analysis are similar.…”
Section: Discussionmentioning
confidence: 99%
“…With the growth of multidisciplinary aerodigestive centers, many patients with persistent pulmonary symptoms undergo triple airway endoscopy as an initial part of their workup before consideration of chest CT. 49 This approach commonly includes flexible bronchoscopy with bronchoalveolar lavage and the results are typically interpreted in the multidisciplinary aerodigestive context. 8,[12][13][14] Prior studies have shown an association between bronchiectasis and BAL neutrophil count and the results our ROC analysis are similar.…”
Section: Discussionmentioning
confidence: 99%
“…1,14 Prior to airway surgery, a triple endoscopy including microlaryngoscopy and bronchoscopy (MLB), upper gastrointestinal endoscopy, and flexible bronchoscopy is commonly performed. 15 MLB remains the gold standard for the diagnosis, quantification, and LTS treatment planning.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…Many children with SGS have additional comorbidities that require multidisciplinary consultation with pediatric surgery, cardiology, cardiothoracic surgery, genetics, neurology, and neurosurgery 1,14 . Prior to airway surgery, a triple endoscopy including microlaryngoscopy and bronchoscopy (MLB), upper gastrointestinal endoscopy, and flexible bronchoscopy is commonly performed 15 . MLB remains the gold standard for the diagnosis, quantification, and LTS treatment planning.…”
Section: Diagnosismentioning
confidence: 99%
“…This allows for complementary modalities for evaluation of upper GI and airway structures and dynamics and facilitates real-time discovery, discussion, and planning amongst all the specialists involved, allowing for excellent, patient-centric care. A consensus on the core data elements to be gathered during triple endoscopy has been published[ 17 ]. From the gastroenterology standpoint, the importance of assessing for EoE is highlighted due to potential contribution to aerodigestive symptoms.…”
Section: Aerodigestive Program Servicesmentioning
confidence: 99%